Black Women Dancers, Jazz Culture, and “Show Biz”: Recentering Afro-Culture and Reclaiming Dancing Black Bodies in Montréal, 1920s–1950s - Jabouin, Emilie (Canadian Journal of History, 2021)
The documentary Show Girls, directed by Meilan Lam, makes an unprecedented contribution to the history of jazz and Black women jazz dancers in Montréal, Quebec, and to the conversation of jazz in Canada. Show Girls offers a glimpse into the lives of three Black women dancers of the 1920s–1950s. This essay asks what the lives of Black women dancers were like and how they navigated their career paths in terms of social and economic opportunities and barriers. I seek to better understand three points: (1) the gap in the study of jazz that generally excludes and/or separates dance and singing from the music; (2) the use of dance as a way to commercialize, sell, and give visual and conceptual meaning to jazz; (3) the importance of the Black body and the role of what I would define as “Afro- culture” in producing the ingenious and creative genre of jazz. My study suggests there is a dominant narrative of jazz, at least in academic literature, that celebrates one dimension of jazz as it was advertised in show business, and that bringing in additional components of jazz provides a counternarrative, but also a restorative, whole and more authentic story of jazz and its origins. More specifically, by re- exploring jazz as a whole culture that relies on music, song, and dance, this essay explores three major ideas. First, Black women dancers played a significant role in the success of jazz shows. Second, they articulated stories of self, freedom, and the identity of the New Negro through jazz culture and dance. Third, Black women’s bodies and art were later crystallized into images that further served to sell jazz as a product of show business.

Black Media Reporting on Theater, Dance, and Jazz Clubs in Canada: From Shuffle along to Rockhead’s Paradise - Thompson, Cheryl; Jabouin, Emilie (Journal of Communication Inquiry, 2021)
Canada has a history of de facto Jim Crow (1911–1954). It also has a historical Black press that is intimately connected to Black America through transnational conversations, and diasporic migration. This article argues that Canada’s Black newspapers played a pivotal role in promoting Black performance during a time when they were scarcely covered in the dominant media. Drawing on news coverage from the 1920s through 1950s of black dance, musicals, and jazz clubs this article examines three case studies: Shuffle Along (1921–1924), the first all- Black Broadway musical to appear at Toronto’s Royal Alexandra Theater, Alberta-born dancer Len Gibson (1926–2008), who revolutionized modern dance in Canada in the 1940s and 1950s, and the Montreal jazz club Rockhead’s Paradise (1928–1980), a pivotal site in the city’s Little Burgundy, a Black neighborhood that thrived in the 1930s through 1950s. The authors argue that when Black people were excluded from and/or derogatorily portrayed in the dominant media, Canada’s Black press celebrated collective achievement by authenticating Black performance. By incorporating Canada’s Black Press into conversations about Jim Crow and performance, we gain a deeper understanding of Black creative output and resistance during the period.